IBM Spectrum Scale functionality to support GDPR requirements - Patil, Sandeep 1986- (IBM Corporation, International Technical Support Organization, 2018)
The role of the IT solutions is to enforce the correct handling of personal data using processes developed by the establishment. Each element of the solution stack must address the objectives as appropriate to the data that it handles. Typically, personal data exists either in the form of structured data (like databases) or unstructured data (like files, text, documents, and so on.). This IBM Redbooks publication specifically deals with unstructured data and storage systems used to host unstructured data. For unstructured data storage in particular, some key attributes enable the overall solution to support compliance with the EU General Data Protection Regulation (GDPR). Because personal data subject to GDPR is commonly stored in an unstructured data format, a scale out file system like IBM Spectrum Scale provides essential functions to support GDPR requirements. This paper highlights some of the key compliance requirements and explains how IBM Spectrum Scale helps to address them.
Date of publication from resource description page. - "In partnership with IBM Academy of Technology.". - "Security.". - Number on back cover: REDP-5489-00. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed October 9, 2019)
Keywords: European Parliament -- General Data Protection Regulation; Cloud computing -- Security measures -- Europe; Business -- Data processing -- Security measures; Business enterprises -- Computer networks -- Security measures; Privacy, Right of; General Data Protection Regulation (European Parliament); Infonuagique; Sécurité; Mesures; Europe; Gestion; Informatique; Sécurité; Mesures; Business; Data processing; Security measures; Business enterprises; Computer networks; Security measures; Europe